Comparison of equipotent doses of Ramosetron, Ondansetron, and sub-hypnotic dose of Propofol for prevention of postoperative nausea and vomiting in laparoscopic cholecystectomy - Shilpa Amol Acharya; Kalyani Nilesh Patil (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: For prevention of Postoperative nausea vomiting (PONV) in laparoscopic surgery, ramosetron is a selective 5-HT3 receptor antagonist with higher receptor affinity and slow dissociation than ondansetron. We compared these 2 drugs with propofol which has also shown antiemetic properties.The aim was to study ondansetron, ramosetron, and propofol with respect to incidence of PONV, its severity and the need for rescue antiemetic along with the side effects. Prospective, randomized, double blind study. Material and Methods: We compared antiemetic properties of ondansetron (4 mg i.v; n = 40) and ramosetron (0.3 mg i.v; n = 40) with propofol (0.5 mg/kg i.v; n = 40) on 120 ASA I/II patients scheduled for laparoscopic cholecystectomy. The side effects associated with study drugs, time to recovery from anesthesia, readiness for PACU discharge and patient satisfaction was also compared. Qualitative data variables are expressed by using frequency and percentage and quantitative data variables are expressed by using mean and SD. Quantitative data variables were compared using ANOVA test and others were compared by post hoc ANOVA Tukey's test. Results: Incidence of vomiting and need for rescue antiemetic was lowest with Ramosetron and highest in Propofol group. Time to recovery was more in Propofol group which was statistically significant. Readiness for PACU discharge was comparable in all the three groups. Conclusion: Subhypnotic dose of propofol requires more rescue antiemetic than Ondansetron and Ramosetron because of its short duration of action. Between Ondansetron and Ramosetron the latter is more effective in PONV prevention.